Integration of Islamic Values in Green Economy-Based Waste Management in Islamic Boarding Schools - Muhtadi Abdul Mun’im; Nur Atika Alias (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The issues raised in this study are related to the environment, which is one of the pressing issues due to its detrimental impacts on humans, ecosystems, and the balance of nature. The urgency of Islamic boarding schools as Islamic educational institutions plays a crucial role in instilling awareness of the importance of maintaining a clean and healthy environment. The concept of Green Economy is oriented towards an economic paradigm that focuses on reducing negative impacts on the natural environment, while also improving social and economic welfare in an inclusive manner. This study aims to analyze how the integration of Islamic values, Green Economy-based waste management, and the role of Islamic boarding schools as agents of change for the community through waste management at the Annuqayah Islamic boarding school in the Lubangsa area. The method used in this study is qualitative with a case study approach aimed at understanding the perspectives of Islamic boarding school residents regarding the integration of Islamic values in Green Economy-based waste management. The data collection techniques used were interviews, observation, and documentation that supported the research focus. Meanwhile, to analyze the data, the author conducted data condensation, data presentation, and drawing conclusions. The results of the study indicate that there are three values ​​integrated in waste management, namely the value of cleanliness, the value of ecological reality, and the value of environmental materials. Green Economy-based waste management is seen in the efficient use of existing resources and the utilization of waste into something valuable, as well as efforts to minimize waste stocks at the Annuqayah Islamic Boarding School in the Lubangsa area. The impact of the Islamic boarding school's role as an agent of change for the community through waste management has an impact on social, economic, and community aspects. The social impact can be seen in changes in the behavior patterns of students and residents who become more disciplined in maintaining cleanliness, the formation of solidarity and social movements in Islamic boarding schools, and the role of students as role models or students become role models. Meanwhile, in the economic aspect, it can be seen in the utilization of waste for productive activities and social entrepreneurship of students. The impact on the surrounding community is increased environmental awareness of residents and Islamic boarding schools as centers of ecological education.